Prevalence of dental paleopathology in a Peruvian pre-hispanic population - Ann Chanamé-Marín; Marco Reátegui-Navarro; Heber Arbildo-Vega (Universidad de Concepción., 2019)
Objective: To determine the prevalence of dental paleopathologies in a Peruvian prehispanic population. Material and Method: A descriptive, observational and transversal study was carried out. The sample consisted of 106 skeletal remains of pre-hispanic inhabitants, over 18 years of age, found in the El Brujo - Magdalena de Cao Archaeological Complex, Lambayeque - Peru. The selection criteria were defined and the presence of dental caries, malocclusion, crowding, dental anomalies of direction and site, age and sex of each bone was assessed using a data collection instrument designed for that purpose. Results: The sample showed presence of dentin caries (62.3%), enamel caries (37.7%), Class I malocclusion (76.4%), Class II malocclusion (4.7%), Class III malocclusion (4.7%), maxillary crowding (15.1%), mandibular crowding (19.8%), crowding in both jaws (13.2%), gyroversion (20.8%), vestibule-versions (15.1%), linguo-versions (17.9%) and dental transposition (5.7%). Conclusion: The results show a high prevalence of caries and malocclusions in this Peruvian pre-hispanic population.